Human dermal fibroblast senescence in response to single and recurring oxidative stress - McCarty, Tailynn Y.; Kearney, Cathal J. (Frontiers in Aging, 2025)
Introduction: Aging results in an accumulation of damaged cells, which reduces the health of tissues and their regenerative capabilities. In the skin, there are both internal and external drivers of oxidative stress that result in aging phenotypes. Oxidative stress has been used to model senescence in vitro; however, there has been a lack of research determining whether the severity of oxidative stress correlates with senescent phenotypes.Methods: In this work, we compare cellular and secretory responses to a single (500 μM hydrogen peroxide, 2 hours) or recurring dose of hydrogen peroxide (500 μM hydrogen peroxide, 2 hours + 4 × 300 μM hydrogen peroxide each 48 hours). Senescence induction was studied using markers including cell morphology, senescence-associated-beta-galactosidase, absence of apoptosis, and cell cycle inhibition genes. Next, functional studies of the effects of the signaling of these cells were completed, such as vascular potential, keratinocyte proliferation, and macrophage polarization.Results: Fibroblasts exposed to both single and recurring oxidative stress had increased total cell and nucleic area, increased senescence-associated-beta-galactosidase (SABGAL) expression, and they were able to escape apoptosis – all characteristics of senescent cells. Additionally, cells exposed to recurring oxidative stress expressed increased levels of cell cycle inhibitor genes and decreased expression of collagen-I, -III, and -IV. Cytokine profiling showed that the single stressed cells had a more inflammatory secretory profile. However, in functional assays, the recurring stressed cells had reduced vascular potential, reduced keratinocyte proliferation, and increased IL-1β gene expression in unpolarized and polarized macrophages.Discussion: The described protocol allows for the investigation of the direct effects of single and recurring oxidative stress in fibroblasts and their secretory effects on surrounding healthy cells. These results show that recurringly stressed fibroblasts represent a more intense senescent phenotype, which can be used in in vitro aging studies to understand the severity of senescent responses.